AIAA Guidance, Navigation, and Control Conference 2009
DOI: 10.2514/6.2009-5904
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Magnetic Locking Flux-Pinned Revolute Joint for Use on CubeSat-Standard Spacecraft

Abstract: Magnetic flux pinning is an interaction between strong magnets and certain superconductors that causes a damped, non-contacting equilibrium to form, connecting the flux-pinned objects. This interaction has been proposed for use in establishing a stable formation of spacecraft modules that is resistant to disturbances. Although flux pinning can exert forces in all six degrees of freedom, a flux-pinned interface can be designed to constrain only certain degrees of freedom so that it functions as a non-contacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…When such a magnetic field is generated by one spacecraft module and a superconductor flux-pinned to that field is mounted on another module, the FPI can function as a revolute joint. Previous work in this area 2,3,8 has confirmed that flux pinning can create joints and other mechanisms, some of which have been validated in both laboratory experiments and during microgravity testing. 9 These mechanisms, when deployed as links on a close formation of spacecraft modules, could allow the spacecraft to easily reconfigure via ground-based commands to electromagnets.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…When such a magnetic field is generated by one spacecraft module and a superconductor flux-pinned to that field is mounted on another module, the FPI can function as a revolute joint. Previous work in this area 2,3,8 has confirmed that flux pinning can create joints and other mechanisms, some of which have been validated in both laboratory experiments and during microgravity testing. 9 These mechanisms, when deployed as links on a close formation of spacecraft modules, could allow the spacecraft to easily reconfigure via ground-based commands to electromagnets.…”
Section: Introductionmentioning
confidence: 69%
“…Air-powered levitation for previous flux pinning experiments was accomplished with the use of an air table which raised experimental vehicles above its surface for unconstrained motion. 8 The primary limitation of this arrangement was that a surface large enough for desirable maneuvers required a prohibitively high input pressure of gas to provide sufficient pressure over the entire surface to support the vehicles. In effect, most of the input gas was not used to support experimental vehicles but expended over empty surface area.…”
Section: A Levitating Base Segmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Flux-pinned interfaces leverage the dynamics of magnetic flux pinning to control the relative orientation and position of close-proximity spacecraft without mechanical contact. These unique traits make flux-pinned interfaces a technology candidate for applications such as spacecraft capture and docking 1,2 , assembly of modular systems 3,4 , formation flying [5][6][7] , kinematic mechanisms 8,9 , and station-keeping 10,11 . However, for this technology to be mature enough for spaceflight applications, its physics must be represented in a high-fidelity predictive dynamics model that can inform design trade and analyses.…”
Section: Introductionmentioning
confidence: 99%